2014
DOI: 10.1371/journal.pone.0095851
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Changes in Nutrients and Mussel Stocks Are Related to Numbers of Breeding Eiders Somateria mollissima at a Large Baltic Colony

Abstract: BackgroundThe Baltic/Wadden Sea eider Somateria mollissima flyway population is decreasing, and this trend is also reflected in the large eider colony at Christiansø situated in the Baltic Sea. This colony showed a 15-fold increase from 1925 until the mid-1990's, followed by a rapid decline in recent years, although the causes of this trend remain unknown. Most birds from the colony winter in the Wadden Sea, from which environmental data and information on the size of the main diet, the mussel Mytilus edulis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 28 publications
2
41
1
Order By: Relevance
“…These changes have negative consequences for bird populations (Bryhn and others 2009). The hypothetical mechanisms linking change in population size of waterbirds to leakage of fertilizer to the marine environment is supported by a recent study of the abundance of blue mussel and its main consumer the eider (Laursen and Møller 2014). Fertilizer use on farmland resulted in increased concentrations of phosphorus, which caused an increase in the production of phytoplankton, which in turn were consumed by mussels.…”
Section: Population Trends and Fertilizer Usementioning
confidence: 99%
See 3 more Smart Citations
“…These changes have negative consequences for bird populations (Bryhn and others 2009). The hypothetical mechanisms linking change in population size of waterbirds to leakage of fertilizer to the marine environment is supported by a recent study of the abundance of blue mussel and its main consumer the eider (Laursen and Møller 2014). Fertilizer use on farmland resulted in increased concentrations of phosphorus, which caused an increase in the production of phytoplankton, which in turn were consumed by mussels.…”
Section: Population Trends and Fertilizer Usementioning
confidence: 99%
“…The addition of nitrogen and phosphorus to marine environments has increased the abundance of benthos (Nixon and Buckley 2002). Laursen and Møller (2014) have recently shown that increased abundance of nutrients in the marine environment caused by leaching from farmland increased the abundance of blue mussels, Mytilus edulis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like other seaducks (Mergini), common eider spring arrival responded to local weather parameters, ice cover, the North Atlantic Oscillation (NAO) index and fertilizer release Jónsson et al 2009;Love et al 2010;Zipkin et al 2010;Laursen and Møller 2014). In northwest Iceland, spring icecover generally is absent but females arrived later following warm winters with strong westerly winds (positive NAO values; Jónsson et al 2009), whereas females in southwest Iceland nested earlier following milder winters (D'Alba et al 2010).…”
Section: Introductionmentioning
confidence: 94%